Orthopedics for Physician Assistant and Nurse Practitioner Students An Introductory Guide - Gracy, John A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This practical introductory guide provides PA/NP students with the tools to recognize and begin treatment of the most common orthopedic problems, to avoid missing critical diagnoses, and to serve as a base of knowledge to which they can add depending on their chosen career path. Utilizing this concise text, PA/NP students will gain a basic familiarity with how to describe a problem (including imaging) to an orthopedic surgeon as well as how to begin treatment. In addition, the student should have no difficulty passing the orthopedic portion of the PA/NP credentialing exams. The essentials of imaging, fracture description and operating room procedures are presented first. Then, proceeding anatomically from upper to lower extremity and the spine, chapters utilize a user-friendly chapter format covering fractures, dislocations and trauma as well as non-traumatic injury, focusing on pathophysiology, diagnosis and differential diagnosis, and brief treatment protocols. Since many PAs are office-based, only the highlights of surgery are presented, with an emphasis on what to look for regarding post-operative complications as well as the goals of the rehabilitation process (both non-operative and post-operative). Many books intended for orthopedic PA/NP students are written for those already in practice, usually providing far more information than the student can absorb in the usual 4-week orthopedic rotation, while others tend to skip important areas. This guide provides concise yet comprehensive coverage for a well-rounded presentation of everything orthopedic PA/NP students need to know to succeed. .
Introduction -- History, Physical Exam and Diagnostic Testing -- The Operating Room -- The Hand and Wrist -- The Elbow and Forearm -- The Shoulder and Humerus -- The Foot and Ankle -- The Knee -- The Hip and Thigh -- The Spine: Cervical, Thoracic, Lumbar -- Tumors -- Pediatric Orthopedics -- Rheumatological Disorders -- Compartment Syndrome.
Keywords: Orthopedics; Sports medicine; Orthopaedics; Sports Medicine; Orthopedic Nursing; Nurse Practitioners -- education; Orthopedic Procedures; Orthopedics; Physician Assistants -- education